An occupational therapy intervention for residents with stroke related disabilities in UK care homes (OTCH): cluster randomised controlled trial. (5th February 2015) - Sackley, Catherine M; Walker, Marion F; Burton, Christopher R; Watkins, Caroline L; Mant, Jonathan; Roalfe, Andrea K; Wheatley, Keith; Sheehan, Bart; Sharp, Leslie; Stant, Katie E; Fletcher-Smith, Joanna; Steel, Kerry; et al.
Abstract : Objective To evaluate the clinical efficacy of an established programme of occupational therapy in maintaining functional activity and reducing further health risks from inactivity in care home residents living with stroke sequelae. Design Pragmatic, parallel group, cluster randomised controlled trial. Setting 228 care homes (>10 beds each), both with and without the provision of nursing care, local to 11 trial administrative centres across the United Kingdom. Participants 1042 care home residents with a history of stroke or transient ischaemic attack, including those with language and cognitive impairments, not receiving end of life care. 114 homes (n=568 residents, 64% from homes providing nursing care) were allocated to the intervention arm and 114 homes (n=474 residents, 65% from homes providing nursing care) to standard care (control arm). Participating care homes were randomised between May 2010 and March 2012. Intervention Targeted three month programme of occupational therapy, delivered by qualified occupational therapists and assistants, involving patient centred goal setting, education of care home staff, and adaptations to the environment. Main outcome measures Primary outcome at the participant level: scores on the Barthel index of activities of daily living at three months post-randomisation. Secondary outcome measures at the participant level: Barthel index scores at six and 12 months post-randomisation, and scores on the Rivermead mobility index, geriatric depression scale-15, and EuroQol EQ-5D-3L questionnaire, at all time points. Results 64% of the participants were women and 93% were white, with a mean age of 82.9 years. Baseline characteristics were similar between groups for all measures, personal characteristics, and diagnostic tests. Overall, 2538 occupational therapy visits were made to 498 participants in the intervention arm (mean 5.1 visits per participant). No adverse events attributable to the intervention were recorded. 162 (11%) died before the primary outcome time point, and 313 (30%) died over the 12 months of the trial. The primary outcome measure did not differ significantly between the treatment arms. The adjusted mean difference in Barthel index score at three months was 0.19 points higher in the intervention arm (95% confidence interval −0.33 to 0.70, P=0.48). Secondary outcome measures also showed no significant differences at all time points. Conclusions This large phase III study provided no evidence of benefit for the provision of a routine occupational therapy service, including staff training, for care home residents living with stroke related disabilities. The established three month individualised course of occupational therapy targeting stroke related disabilities did not have an impact on measures of functional activity, mobility, mood, or health related quality of life, at all observational time points. Providing and targeting ameliorative care in this clinically complex population requires alternative strategies. Trial registration Current Controlled Trials ISRCTN00757750 .